Self-organizing coalitions for managing complexity : agent-based simulation of evolutionary game theory models using dynamic social networks for interdisciplinary applications /: agent-based simulation of evolutionary game theory models using dynamic social networks for interdisciplinary applications. (2018) - Burguillo, Juan C
No abstract available